2019
DOI: 10.18502/cmm.5.2.1161
|View full text |Cite
|
Sign up to set email alerts
|

Onychoscopic evaluation of distal and lateral subungual onychomycosis: A cross-sectional study in Lebanon

Abstract: Background and Purpose: The aim of this study was to evaluate the onychoscopic patterns associated with distal lateral subungual onychomycosis (DLSO) in Lebanon. Materials and Methods: The present study was conducted on 45 patients with clinical DLSO attending two dermatology clinics in Beirut, Lebanon, between January 2018 and April 2018. The patients were subjected to dermoscopy to identify the onychoscopic patterns. Results: The DLSO was predominantly associated with white, yellow, and brown color changes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Onychoscopy of onychomycosis typically shows the jagged shape with sharp structures (spikes) of the proximal margin of the onycholysis, 58,59 the colours of the onycholytic nail, which resemble the aurora borealis pattern, 1 and the ruin-like appearance of the subungual area. 60,61 The gold standard of KOH microscopy and fungal culture for diagnosis of onychomycosis is currently being questioned. KOH microscopy has a false-negative rate ranging from 5% to 15% and may give a false-positive during treatment efficacy analysis, as both dead and live hyphae are visually indistinguishable from one another.…”
Section: Diagnostic Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Onychoscopy of onychomycosis typically shows the jagged shape with sharp structures (spikes) of the proximal margin of the onycholysis, 58,59 the colours of the onycholytic nail, which resemble the aurora borealis pattern, 1 and the ruin-like appearance of the subungual area. 60,61 The gold standard of KOH microscopy and fungal culture for diagnosis of onychomycosis is currently being questioned. KOH microscopy has a false-negative rate ranging from 5% to 15% and may give a false-positive during treatment efficacy analysis, as both dead and live hyphae are visually indistinguishable from one another.…”
Section: Diagnostic Techniquesmentioning
confidence: 99%
“…Onychoscopy, also known as nail dermoscopy, gives important clues for the diagnosis of onychomycosis and allows differential diagnosis with other non‐mycotic nail diseases. Onychoscopy of onychomycosis typically shows the jagged shape with sharp structures (spikes) of the proximal margin of the onycholysis, 58,59 the colours of the onycholytic nail, which resemble the aurora borealis pattern, 1 and the ruin‐like appearance of the subungual area 60,61 …”
Section: Diagnostic Techniquesmentioning
confidence: 99%
“…Nineteen studies reported dermoscopic features of 1,693 cases of onychomycosis. Commonly identified dermoscopic features of onychomycosis were spikes or spiked pattern (481, 28.4%) ( 10 – 18 ), jagged or spiked edges or jagged edge with spikes (188, 11.1%) ( 19 25 ), jagged proximal edge (175, 10.3%) ( 10 , 12 , 16 , 18 ), subungual hyperkeratosis (131, 7.7%) ( 15 , 19 , 20 , 25 , 26 ), ruins appearance, aspect or pattern (573, 33.8%) ( 15 , 19 , 22 , 24 , 27 , 28 ), and longitudinal striae (929, 54.9%) ( 10 – 18 , 20 23 , 27 ) ( Table 2 ). Other dermoscopic findings included distal irregular termination (331, 19.6%) ( 10 12 , 14 16 , 18 , 20 , 22 ) and aurora borealis pattern (293, 17.3%) ( 11 , 12 , 15 , 17 , 20 , 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…Commonly identified dermoscopic features of onychomycosis were spikes or spiked pattern (481, 28.4%) ( 10 – 18 ), jagged or spiked edges or jagged edge with spikes (188, 11.1%) ( 19 25 ), jagged proximal edge (175, 10.3%) ( 10 , 12 , 16 , 18 ), subungual hyperkeratosis (131, 7.7%) ( 15 , 19 , 20 , 25 , 26 ), ruins appearance, aspect or pattern (573, 33.8%) ( 15 , 19 , 22 , 24 , 27 , 28 ), and longitudinal striae (929, 54.9%) ( 10 – 18 , 20 23 , 27 ) ( Table 2 ). Other dermoscopic findings included distal irregular termination (331, 19.6%) ( 10 12 , 14 16 , 18 , 20 , 22 ) and aurora borealis pattern (293, 17.3%) ( 11 , 12 , 15 , 17 , 20 , 23 ). Frequently described color changes were homogenous leukonychia (304, 18.0%) ( 12 , 15 , 16 , 20 , 22 , 23 , 28 ), yellow (216, 12.8%) ( 13 , 15 , 16 , 23 , 26 ) and brown (212, 12.5%) ( 12 , 15 , 16 , 22 , 23 , 26 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation